If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -7x + 33 = 5x + 26 Reorder the terms: 33 + 5x + -7x = 5x + 26 Combine like terms: 5x + -7x = -2x 33 + -2x = 5x + 26 Reorder the terms: 33 + -2x = 26 + 5x Solving 33 + -2x = 26 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 33 + -2x + -5x = 26 + 5x + -5x Combine like terms: -2x + -5x = -7x 33 + -7x = 26 + 5x + -5x Combine like terms: 5x + -5x = 0 33 + -7x = 26 + 0 33 + -7x = 26 Add '-33' to each side of the equation. 33 + -33 + -7x = 26 + -33 Combine like terms: 33 + -33 = 0 0 + -7x = 26 + -33 -7x = 26 + -33 Combine like terms: 26 + -33 = -7 -7x = -7 Divide each side by '-7'. x = 1 Simplifying x = 1
| 4cost^2-3cosx=0 | | 8x+4x-7x=5+1 | | x^2+y^2+6x-2y+16=0 | | 4x^3+18x^2+24x+9=0 | | 8(x-5)=-49 | | 19t+39=V | | V=19t+39 | | 14t^2=a | | 5x-x-8=3x-6 | | 14+4(6c-3)= | | 8x+40=-4x+7 | | a=14t^2 | | ysqrt(1-x^2)dx+xsqrt(1-y^2)dy=0 | | -46-5x-1/3x | | 5ln(x-2)=1 | | 5x^2+5xy-3.3=0 | | 5x-2+7x=5 | | -3(x-1)+4x=12 | | 5(x-6+3)=-7 | | 5(6z-1)-2(z+8)=17(z+1) | | 4(3-4)= | | 268/340*100 | | 3x-5=2(x+3)+x | | f(x+3)=x^2+7x+5 | | m-6m-2m-5=0 | | 48-4x=4x | | 3(7s+6)-13s=2(4s+5)-12 | | 0.13x+0.9(x-5)=0.01(2x-3) | | 0.10(y-3)+0.18y=0.08y-0.7 | | 2d+13=d+1 | | 10f+37=-23 | | 0.12x+0.3(x-2)=0.01(5x-4) |